Evaluasi Efektivitas Sistem Monitoring Berkala dalam Peningkatan Kinerja Teknis Temporary Stockpile di PT Bukit Asam Tbk - Satrio Fetriawan; Maulana Yusuf; Taufik Toha (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Periodic technical monitoring of temporary stockpiles is required to support operational control and continuous improvement in coal mining activities. This evaluation aims to assess whether technical assessment results can indicate operational improvement over time at PT Bukit Asam Tbk. The method used is quantitative descriptive analysis based on internal monitoring reports from July 2025 to May 2026. The analysis was conducted by comparing average scores, dominant technical findings, and changes in improvement recommendations. The results show that the average score increased from the baseline of 75.26 in July 2025, reached the lowest post-baseline point of 79.62 in October 2025, and reached the highest value of 84.26 in May 2026. All post-baseline periods remained above the initial score, indicating medium-term technical improvement despite fluctuating field conditions. The monitoring system is effective as an evaluation and operational control tool; however, further development is required to produce a more comprehensive assessment system.